Effects of gender, age, and nutrition on circadian locomotor activity rhythms in the flesh fly Sarcophaga crassipalpis. (May 2018) - Prohaska, Fritz; Joplin, Karl H.; Moore, Darrell
Graphical abstract: Highlights: Females show higher activity levels, in both photophase and scotophase, than males. Females temporarily depart from diurnality by showing extended dark activity (EDA). The age of occurrence of EDA is related to liver availability. The entrainment profiles differ between males and females. No significant sex- or nutrition-related differences in circadian period were found. Abstract: In many animal species, circadian rhythms of behavior are not constant throughout the lifetime of the individual but rather exhibit at least some degree of plasticity. In the present study, we have examined the potential influences of gender, age, and nutrition (presence or absence of liver) on the expression of circadian locomotor activity rhythms in the flesh fly Sarcophaga crassipalpis . We found no significant differences in endogenous circadian period under constant dark conditions with respect to gender, nutrition, or age for the duration of our experiments. On the other hand, both male and female flesh flies, as expected, were predominantly diurnal under light-dark cycles, but the pattern of entrainment differed between the sexes. Females also displayed higher activity levels than males. Also, in contrast with males, female activity levels increased with age. Moreover, females exhibited an extraordinary, but transient (one to three days), departure from diurnality which we characterize as "extended dark activity" (EDA). This phenomenon appeared as a continuous bout of locomotor activity that extended at least three hours into the early half of the dark phase at levels at least twice the median of the overall locomotor activity for the individual fly. EDA occurred as an age-dependent response to liver consumption, never appearing prior to day 4 post-eclosion but, thereafter, transpiring within one or two days after a 48-h exposure to liver. These results suggest a linkage between physiological events associated with egg provisioning and locomotor activity in the anautogenous flesh fly. Furthermore, our findings identify the existence of multiple influences on the expression of circadian clock-regulated behavior.